Association between acculturation and sociodemographic factors and cardiovascular disease among immigrants to the United States. Issue 1 (26th October 2020) - Hopgood, Daniel A.; Haile, Zelalem T.; Conley, Sean; Chertok, Ilana R. A.
Abstract: Objective: This study investigated relationships among acculturation, sociodemographic, and health characteristics of adult U.S. immigrants and cardiovascular disease. Design: Secondary data analysis using population data from 1, 945 immigrant participants in the 2017 National Health Interview Survey (NHIS). Measurements: Acculturation was measured using citizenship status, number of years in the U.S., and English language proficiency. Chi‐square tests and multiple logistic regression modeling were utilized. Results: Approximately 4.3% of the study sample had cardiovascular disease. Compared to immigrants without U.S. citizenship, significantly higher proportion of immigrants with U.S. citizenship had cardiovascular disease (6.2% vs. 1.7%, p < .001). In the multivariable‐adjusted model, compared to non‐citizen immigrants, odds of cardiovascular disease were higher in immigrants with U.S. citizenship (odds ratio 3.80, 95% confidence interval 1.91, 7.56). Conclusion: Acculturation factors, specifically U.S. citizenship, along with sociodemographic and health risk factors were associated with increased odds of cardiovascular disease among immigrants. This study builds upon previous findings demonstrating increased acculturation including U.S. citizenship in immigrant populations is associated with increased odds of cardiovascular disease. These findings inform public health specialists and clinicians of factors to consider for cardiovascular disease risk in immigrants as they adapt to their host country.